2017
DOI: 10.7860/jcdr/2017/24559.9433
|View full text |Cite
|
Sign up to set email alerts
|

A Community Based Study on Pelvic Inflammatory Disease in Postmenopausal Females: Microbiological Spectrum and Socio- Demographic Correlates

Abstract: Introduction: Pelvic Inflammatory Disease (PID) is a common and serious complication of sexually transmitted diseases in young women but is rarely diagnosed in the postmenopausal women. Very few studies have been done regarding postmenopausal PID. Aim:To determine the burden of PID, associated micro-organisms, pathophysiology and risk factors among post-menopausal women of the community. Materials and Methods:A cross-sectional study was conducted among 530 post-menopausal women in the registered field practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…In ammation is theorized to play a role in the pathogenesis of age-related chronic diseases [3]. Similarly, epidemiological studies have demonstrated a connection between POP and immune-mediated diseases [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In ammation is theorized to play a role in the pathogenesis of age-related chronic diseases [3]. Similarly, epidemiological studies have demonstrated a connection between POP and immune-mediated diseases [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Em um estudo transversal de base comunitária dirigido porKhan et al, (2017), no qual se analisou a prevalência de DIP em mulheres na pósmenopausa, foi encontrada uma prevalência média de 11,55% da doença, já que a menopausa resulta na diminuição da colonização. Entretanto, essa prevalência foi ligada, principalmente, à vaginose bacteriana, lesões intraepiteliais do colo do útero e ao próprio comportamento de mulheres mais velhas, já que não se expõem mais a tantos fatores de risco, como múltiplos parceiros e instrumentação uterina.De acordo comCostalira et al, (2017), em Manaus, situado no estado do Amazonas, germe infeccioso mais frequente nas mulheres com vida sexualmente ativa, em qualquer faixa etária, envolvida com causadores de DIP foi a Clamídia trachomatis.Além disso,Jennings et al, (2020) relata que, em relação à incidência de DIP, a ocorrência é maior em mulheres com idades entre 15 e 25 anos.…”
unclassified